The impacts of animal farming: A critical overview of primary school textbooks - Fonseca, R. P. (Journal of Agricultural and Environmental Ethics, 2022)
Based on a sample of 46 Portuguese schoolbooks, this study aims to understand how factory-farmed animals are presented in such books across the themes of food and health, the environment and sustainability, and animal welfare. It examines whether schoolbooks address the importance of reducing the consumption of animal-based products for a healthy diet, whether plant-based diets are recognized as healthy, whether animal welfare and agency are considered, and whether the livestock sec- tor is indicated as a major factor in environmental degradation. The findings show that schoolbooks present animals as essential for economic activities and human nutrition. Recommendations on reducing the consumption of animal-based products in consideration of the environment, sustainability and human health are very rare. Animal production is presented as benign, and the agency and welfare of factory- farmed animals are simply not addressed